Dinâmica do crescimento do meloeiro rendilhado ‘Fantasy’ cultivado em substrato sob ambiente protegido - Danilo Mesquita Melo; Hamilton César de Oliveira Charlo; Renata Castoldi; Leila Trevisan Braz (Biotemas)
http://dx.doi.org/10.5007/2175-7925.2014v27n2p19